The Use of Problem Based Learning (PBL) Method to Improve Students' Understanding of Asmaul Husana Material at SD Negeri 0901 Tanjung Baringin - Dewi, Yunita (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the understanding of grade 5 students of SD Negeri 0901 Tanjung Baringin, on the material of Asmaul Husna through the application of the Problem Based Learning (PBL) method. The PBL method was chosen because it is able to encourage students to actively participate in the learning process, think critically, and develop problem-solving skills. This study uses a classroom action research (CAR) design which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of the study were 30 grade 5 students who were observed during the learning process. Data were collected through observation, interviews, and student understanding tests before and after the application of PBL. Data analysis was carried out by comparing test scores before and after the action, and analyzing the results of observations to see the development of student involvement. The results of the study showed that the application of the PBL method can improve students' understanding of the material of Asmaul Husna. The average test score of students increased from 65 in the pre-action to 85 in the second cycle. In addition, the level of student participation in discussions and group activities also increased significantly. Thus, it can be concluded that the Problem Based Learning method is effective in improving students' understanding of the subject matter, especially Asmaul Husana.